Platinum and Palladium Bio-Synthesized Nanoparticles as Sustainable Fuel Cell Catalysts - Stephen, Alan J.; Rees, Neil V.; Mikheenko, Iryna; Macaskie, Lynne E. (Frontiers in Energy Research, 2019)
A hydrogen economy powered by fuel cells is emerging as an alternative to the current fossil-fuel based energy system where hydrogen, produced through renewable sources, is used to generate electricity via fuel cells. A commonly investigated fuel cell, the Polymer Electrolyte Fuel Cell (PEMFC), usually uses platinum and other platinum group metal nanomaterials to catalyze the rate limiting Oxygen Reduction Reaction (ORR) of this process. The high prices and durability limitations of these catalysts have prevented their mass commercialization. Biosynthesis of nanomaterials has emerged as a potentially attractive “eco-friendly” alternative to conventional chemical synthesis methods. Various attempts have been made to biosynthesize nanoparticles for use in fuel cells. However, the processing methods used during and post synthesis increase their costs and limit their overall efficacies. We report bimetallic Pt/Pd nanoparticles (NPs) biosynthesized by E. coli [E. coli-Pt/Pd (10 wt%:10 wt%)] that shows promise for direct use as a PEMFC catalyst. This catalyst outperformed single metal versions of the same, i.e., E. coli-Pt (20 wt%) and E. coli-Pd (20 wt%) when tested as an electrocatalyst ex-situ. Direct use of E. coli-synthesized nanoparticles in PEMFCs is limited by the inherent resistances of the bacteria and the internal localization of nanoparticles. Transmission electron microscopy images and impedances (resistivity) tests showed that by initially synthesizing Pd nanoparticles on the E. coli cells, followed by Pt, gave a cell surface-localized metallic shell that improved conductivity of the catalyst. Catalyst Pt synthesis is likely mediated by initially-formed Pd-NPs reducing Pt (IV) under H2 resulting in alloying; this was evidenced by XRD data that showed XRD peaks for E. coli-Pt/Pd (10%:10%) which lie in between XRD peaks for Pt-only and Pd-only nanoparticles on the same planes. Protrusions of agglomerated nanoparticles were seen on the cell surface to form sites for catalytic activity. The catalyst, used in the ORR without optimization, performed significantly worse (~100 times) than a commercial catalyst (extensively developed for purpose) but which contained 5 times as much Pt. This serves as a starting point for a more engineered approach to bio-synthesizing nanoparticles for PEMFC catalysts.